Pengembangan Media Pembelajaran Interaktif Articulate Storyline Berbasis Pendekatan Saintifik Pada Materi Ekosistem Kelas V SD Negeri 066054 Kec. Medan Denai - Afnisah, Nur; Ananda, Lala Jelita; Siregar, Arifin; Simanjuntak, Eva Betty; Gandamana, Apiek (Universitas Labuhanbatu, 2023)
Research background at SD Negeri 066054 Kec. Medan Denai found several problems namely; 1) Learning media on Ecosystem Material in Class V SD Negeri 066054 Kec. Medan Denai is still an image medium due to a lack of innovation; 2) Teachers are not yet optimal in developing digital learning media; 3) The results of students' daily tests are still incomplete on ecosystem learning materials; 4) Students are more interested if learning uses learning media. The purpose of this research is to produce Articulate Storyline learning media that is valid, practical, and effective for fifth grade students at SDN 066054 Kec. Denai Field. This type of research is R & D (Research and Development) research using the ADDIE development model. The steps of this research and development are Analyze, Design, Development, Implementation, and Evaluation. The test subjects consisted of material experts, media experts, practitioner experts, fifth grade teachers and 27 students for the field trials. Data collection techniques in this study were observation, interviews, questionnaires and tests. Data analysis techniques in this study are descriptive qualitative and quantitative descriptive analysis techniques. The results of the development of Articulate Storyline media show (1) The results of the validation of material experts as a whole show that the learning media is stated to be very valid (87.5%) and the results of the validation of the media as a whole are very valid qualifications (92.5%); (2) The results of the practicality of the teacher as a whole show that the learning media is stated to be very practical (95%); (3) The results of the effectiveness test have an average value of 83.33 with the